The Humanitarian as Negotiator: Developing Capacity Across the Aid Sector. Issue 1 (14th January 2020) - Grace, Rob
Abstract : This article examines the dynamics at play in ongoing efforts to cultivate negotiation capacity among professionals working in the humanitarian sector. Based on extensive semi‐structured interviews conducted with humanitarian practitioners, this article discusses six particular challenges that aid agencies face. The first is raising awareness across the aid sector that negotiation is a core competency of humanitarian action. The second is grappling with ambiguities around the definition of the term "humanitarian negotiation." The third is cultivating an appreciation for the holistic range of negotiation capital that is necessary for success. The fourth is navigating the difficulties inherent in the experiential nature of negotiation capacity building. The fifth is discerning which lessons should be learned from past humanitarian negotiation practice. The sixth is mitigating negative unintended effects of directing professional and policy attention toward humanitarian negotiation capacity building. Through this examination, the article aims to assess the landscape of current humanitarian negotiation capacity‐building efforts, as well as the difficulties that humanitarian organizations will likely face on the road ahead.